Value Management (VM): A Strategic Approach for Improving Energy Efficiency - Mohamad Zamhari Tahir; Mohd Nasrun Mohd Nawi; Amlus Ibrahim (International Journal of Supply Chain Management, 2016)
Value Management (VM) is a multi-disciplinary process, consist of team oriented, structured, analytical process and systematic analysis of function, to seeks best value in the project process and meet the clients needs. While the important of Energy Efficiency (EE) in buildings is a must nowadays because of energy consumption rising very high and this situation occurs not only in developed countries but also in developing countries such as Malaysia. In fact, there is demand towards building with energy efficiency features at this time, however most of the current buildings types are still being constructed with conventional designs thus contribute to inefficient of energy consumption during the operation stage of the building. Based on the relevant literatures, VM has provides an efficient and effective delivery system to fulfil the objectives and clients requirements. Therefore, this paper presents the concept and the application of VM approach and potential to improve energy efficiency within pre-construction process and contribute to better optimize the energy consumption in a building by seeking the best value energy efficiency through the design and construction process.